Ascorbic acid in skin health - Ravetti, Soledad (2019)
Ascorbic acid (vitamin C) is a water-soluble vitamin and a recognized antioxidant drug that is used topically in dermatology to treat and prevent the changes associated with photoaging, as well as for the treatment of hyperpigmentation. Ascorbic acid has neutralizing properties of free radicals, being able to interact with superoxide, hydroxyl and free oxygen ions, preventing the inflammatory processes, carcinogens, and other processes that accelerate photoaging in the skin. Current research focuses on the search for stable compounds of ascorbic acid and new alternatives for administration in the dermis. Unlike plants and most animals, humans do not have the ability to synthesize our own ascorbic acid due to the deficiency of the enzyme L-gulono-gamma-lactone oxidase, which catalyzes the passage terminal in the ascorbic acid biosynthesis. To deal with this situation, humans obtain this vitamin from the diet and/or vitamin supplements, thus preventing the development of diseases and achieving general well-being. Ascorbic acid is involved in important metabolic functions and is vital for the growth and maintenance of healthy bones, teeth, gums, ligaments, and blood vessels. Ascorbic acid is a very unstable vitamin and is easily oxidized in aqueous solutions and cosmetic formulations. Ascorbic acid is extensively used as an ingredient in anti-aging cosmetic products, as sodium ascorbate or ascorbyl palmitate. This review discusses and describes the potential roles for ascorbic acid in skin health and their clinical applications (antioxidative, photoprotective, anti-aging, and anti-pigmentary effects) of topical ascorbic acid on the skin and main mechanisms of action. Considering the instability and difficulty in administering ascorbic acid, we also discuss the importance of several factors involved in the formulation and stabilization of their topical preparations in this review.